Serial Proton MR Spectroscopic Imaging of Recurrent Malignant Gliomas after Gamma Knife Radiosurgery - Graves, Edward E.; Nelson, Sarah J.; Vigneron, Daniel B.; Verhey, Lynn; McDermott, Michael; Larson, David; Chang, Susan; Prados, Michael D.; Dillon, William P. (American Journal of Neuroradiology, 2001)
BACKGROUND AND PURPOSE: The diagnosis of brain tumors after high-dose radiation therapy is frequently limited by the lack of metabolic discrimination available with conventional imaging methods. The purpose of this study was to use proton MR spectroscopy to investigate serial changes in recurrent malignant gliomas after gamma knife radiosurgery to characterize tissue response to high-dose radiation.METHODS: Eighteen patients with recurrent gliomas were studied with MR imaging and 3D proton MR spectroscopic imaging at the time of radiosurgery and at regular time points thereafter. Choline (Cho) and N-acetyl aspartate levels were calculated on a voxel-by-voxel basis and compared with levels found in normal tissue and with levels observed at previous time points. The results of the spectral analysis were then compared with the radiologic findings. Statistical comparisons were precluded by the small sample sizes involved.RESULTS: Response within the gamma knife target was observed as a reduction of Cho levels and an increase in lactate/lipid levels, typically within 6 months of treatment. Increases in Cho correlated with poor radiologic response and suggested tumor recurrence, confirmed histologically in six cases. The development of a spectral abnormality preceded a coincident increase in contrast enhancement by 1 to 2 months in nine cases.CONCLUSION: Proton MR spectroscopic imaging provided diagnostic and monitoring information before and after radiosurgery. Evaluation of metabolic changes with proton MR spectroscopy and structural changes with MR imaging improved tissue discrimination and provided correlation with histologic findings.